Uji Model SerQual pada Perguruan Tinggi: Survey Empiris Mutu Layanan dan Kepuasan Mahasiswa Fakultas Ekonomi Universitas Widya Dharma Klaten - Dandang Setyawanti; Anis Marjukah; Abdul Haris; M Suranto; Agung Nugroho Jati; M Pujo Darmo (MAMEN: Jurnal Manajemen, 2022)
This study aims to analyze the students’ Faculty of Economics Universitas Widya Dharma satisfaction index by analyzing the gaps in each element of service. The research method is quantitative with the test of gap between expectation and perception of service quality. The respondents were 170 students in the three study programs with purposive sampling technique. The quantitative test was conducted in the form of validity test, item reliability, and Servqual gap test. The research finding shows that all dimensions have a gap value with the largest gap value in the physical evidence dimension. Lecturers and education staff  in Economics Faculty Unwidha must be able to improve the service quality with the priority improvements starting from the largest gap value so the students’ satisfaction is created